Val/Met polymorphism in metformin response gene OCT1 in Lima and Puno samples. Pharmacogenetic approach of diabetes - Olivares, Luis (2017)
Introduction: Pharmacogenetics can be used in clinical analysis to assess the efficiency of drugs according to the patient’s genetic profile, and it is becoming important for population genetics and precision medicine. The type 2 diabetes mellitus (T2DM) is highly prevalent all over the world, including Peru. Among the different drugs for T2DM, metformin is used the most and patient’s response to it can be influenced by the Val/Met polymorphism of the OCT1 (SLC22) gene, where Met is associated with a lower response. The frequencies of these polymorphisms vary according to ethnic origin. Objective: To evaluate the distribution of the Val/Met polymorphism in the OCT1 gene in samples of Lima and Puno, and to assess their impact on pharmacogenetics of T2DM. Design: Descriptive, cross-sectional study. Settings: Faculties of Pharmacy and Biochemistry, and Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru; Centro de Genética y Biología Molecular, Facultad de Medicina, Universidad de San Martín de Porres, Lima, Peru. Participants: DNA samples of 56 non-selected subjects from Puno and 57 from Lima regions. Interventions: Analysis of the Val/Met polymorphism in OCT1 gene using the PCR-RFLP technique. Main outcome measures: Phenotypic and allelic frequencies. Results: Genotype frequencies were Val/Val=85,0% and Val/Met=15,0%. The Val allele frequency was higher than 93%, the Met allele was associated with a lower response to metformin and was present in Amantaní (8.3%) and in Lima (9.6%), and absent in Taquile. Conclusions: We found the highest Val allele frequency in the world. Regarding the Met allele, less frequent, we found differences among the Peruvian subpopulations tested, and this knowledge can help in the pharmacogenetics and decision making about oral treatment of metformin against diabetes.